"Coerced Loss and Ambivalent Preservation": Racial Melancholia in American Born Chinese. Issue 1 (February 2017) - Sarigianides, Sophia Tatiana
Abstract: Recent applications of Freud's theory examine the social value of the lost love object as a way of understanding the suffering of non‐majority groups. Rather than pathologizing the individual suffering the loss, the lens of racial melancholia pathologizes the discourse that constitutes racially marked others as alien to the majority. Through a close reading of image and text, Sophia Tatiana Sarigianides applies David Eng and Shinhee Han's theory of racial melancholia to Gene Luen Yang's graphic novel American Born Chinese . Sarigianides argues that texts such as American Born Chinese provide grounds for a public language for examining the suffering that ensues from the failure of assimilation as a desired outcome for immigrants in the United States.